Republic of Argentina Financial Sector Assessment : IOSCO Objectives and Principles of Securities Regulation - International Monetary Fund; World Bank (Washington, DC, 2017)
This assessment finds that Argentina has made significant progress to improve its securities regulatory system within the existing legal framework. Specifically, Argentina operates a highly, even uniquely, transparent securities regulatory program. The assessment also finds that the Argentine securities regulator has dedicated professional staff, active on-site inspection programs, pro-active investigation of complaints, a road map to transition by 2012 to international accounting standards (IFRS) and plans to modernize auditing standards, the ability to assist foreign regulatory authorities to the extent of its current powers, and a commitment to use the powers it has to meet its mandate, achieve international benchmarks, and build on its practical experience to strengthen regulatory oversight. At the same time this assessment finds areas, of which the securities regulator is well aware, that need to be improved. These include that: (i) the complex structure of the market may be a source of inefficiency and an impediment to price formation and best execution; (ii) the regulator has insufficient administrative power to oversee comprehensively the regulatory performance by certain self-regulatory organizations affecting equity and private debt markets with respect to their members and to supervise, discipline and enforce its rules and the securities laws over such members directly; (iii) the ability to cooperate domestically and with foreign regulators is constrained by securities and banking secrecy law; (iv) the legal underpinning for protecting customer funds held by intermediaries needs enhancements; (iv) there are no existing market disruption contingency plans at the regulatory level; and (v) the markets offer some products that may require additional, tailored monitoring and explanation to external participants. This assessment of the International Organization of Securities Commissions (IOSCO) objective and principles of securities regulation was conducted between May 11 and May 26, 2011 in Buenos Aires, Argentina and includes references to certain post on-site improvements. The assessment included a review of the main securities laws, executive decrees, and general resolutions that relate to the mandate of the Comision Nacional de Valores (CNV) and underpin the public offer and trading of securities in Argentina.